2021
DOI: 10.1155/2021/5340449
|View full text |Cite
|
Sign up to set email alerts
|

Hub Genes and Key Pathways of Intervertebral Disc Degeneration: Bioinformatics Analysis and Validation

Abstract: Objective. To identify significant pathways and genes in intervertebral disc degeneration (IDD) based on bioinformatics analysis. Design. The GEO database was used to download the GSE124272 dataset. Differentially expressed genes (DEGs) were analyzed using Limma package in R language. Then, gene ontologies (GO), Kyoto encyclopedia of genes and genomes (KEGG), and protein-protein interaction (PPI) networks were used to further identify hub genes. The mRNA expression levels of top six hub genes were verified. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…In contrast, KEGG analysis was mainly enriched in the TGF beta signaling pathway, toll-like receiver signaling pathway, TNF signaling pathway, and other pathways. This is essentially the same as the results of the previous study [ 37 , 38 ]. The main pathological changes in IDD are apoptosis of the NPCs and degradation of the extracellular matrix [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, KEGG analysis was mainly enriched in the TGF beta signaling pathway, toll-like receiver signaling pathway, TNF signaling pathway, and other pathways. This is essentially the same as the results of the previous study [ 37 , 38 ]. The main pathological changes in IDD are apoptosis of the NPCs and degradation of the extracellular matrix [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Zhao et al demonstrated that KIF20A can promote tumor cell proliferation and inhibit apoptosis in vivo and in vitro (37). Likewise, Zhang et al [60] confirmed that the mRNA levels of KIF20A were upregulated in degenerative NP tissue than in healthy NP tissue (38). These findings indicate that KIF20A may be a novel target associated with NP cell degeneration.…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, Zhang et al. [60] confirmed that the mRNA levels of KIF20A were upregulated in degenerative NP tissue than in healthy NP tissue ( 38 ). These findings indicate that KIF20A may be a novel target associated with NP cell degeneration.…”
Section: Discussionmentioning
confidence: 89%
“…Khan et al (22) showed that the 3-phosphoinositol-dependent protein kinase (PDK) can promote chondrocyte apoptosis in OA through the p38 MAPK signaling pathway (23,24), while Yang et al (25) found DUal-specificity phosphatase (DUSP) overexpression in OA inhibited the activation of MAPK signaling and the expression of the OA-associated matrix. Zhang et al (26) revealed the JAK/STAT signaling pathway was regulated by significantly upregulated by proinflammatory cytokine gene expression, while MMP-13 expression in the IL-1treated human chondrosarcoma cell lines induced JAK2 and STAT1/STAT2 activation and MMP-13 gene expression which was blocked by the pan-tyrosine kinase inhibitor AG490 (27)(28)(29)(30). However, it was also found that treatment of this chondrocyte line with IL-1 also activated p38-MAPK.…”
Section: Discussionmentioning
confidence: 98%